CHARACTER BUILDING STRATEGIES BASED IN ISLAMIC RELIGIOUS EDUCATION AT ELEMENTARY SCHOOL - Rofiatul Hosna; Royyanatul Mahbubah; Egara Dinnul Iza; Fina Fauziyah (Al-Mudarris: Journal Of Education, 2025)
Globalization has had a significant impact on the development of the character of the younger generation, including in Indonesia. One of the negative effects is the decline in morals, which leads to deviant behavior among teenagers. Therefore, character education becomes crucial in shaping a generation with good morals. The Merdeka Curriculum serves as a foundation for implementing a more comprehensive character education in schools. This study aims to analyze the strategy of character development through the implementation of the Merdeka Curriculum in Islamic Religious Education at Madrasah Ibtidaiyah An-Nur Pamekasan. This research uses a qualitative approach with a descriptive method, collecting data through interviews, observations, and documentation. The results show that the implementation of the Merdeka Curriculum in this madrasah is effective in developing students' character, with an approach that integrates the values of Pancasila and reinforces religious habits. The inculcation of character values such as discipline, responsibility, and cooperation is embedded through various learning activities and daily school routines. This study provides an important contribution to understanding the role of the Merdeka Curriculum in character education at the elementary education level.